POLY(VINYL ALCOHOL) HYDROGEL AS AN ULTRASONIC CALIBRATION PHANTOM MATERIAL - Puspitasari, Dita
calibration phantom is a device that is used to ensure the quality of the ultrasonic transducer. The phantom material must have similar acoustic properties to the soft tissues of a human. Poly(vinyl alcohol) (PVA) is a candidate material that can fulfill these properties, but the stability of PVA phantom for repeated testing in ultrasonic transducer calibration has not been much inspected. This research focuses on the manufacturer of PVA-based phantom using the freezing-thawing method for 4 cycles to form a stable hydrogel through non-covalent crosslinking. A rubber ball with a diameter of 3,1 cm was chosen as the target material which was implanted into the PVA phantom. Ultrasonic measurements were carried out with a linear transducer at 3 different times (1, 2, and 4 weeks) to determine the stability of the resulting image. Four different frequencies (5, 6,5, 7,5, and 10 MHz) were applied in ultrasonic image measurement. Ultrasonic testing shows that the phantom temperature before testing affects the resulting image. The clearest target image boundaries are shown at low frequencies (5 and 6,5 MHz) in the second week because of the effect of adding aquadest couplant in each measurement. The diameter of the target was measured from the ultrasonic images and processed by MATLAB with a ratio of 76,4%-95,8% from the actual diameter.